Congenital disorder of glycosylation type Ia presenting with hydrops fetalis. Issue 4 (8th December 2006) - van de Kamp, J M; Lefeber, D J; Ruijter, G J G; Steggerda, S J; den Hollander, N S; Willems, S M; Matthijs, G; Poorthuis, B J H M; Wevers, R A
Abstract : There is a growing awareness that inborn errors of metabolism can be a cause of non-immune hydrops fetalis. The association between congenital disorders of glycosylation (CDG) and hydrops fetalis has been based on one case report concerning two sibs with hydrops fetalis and CDG-Ik. Since then two patients with hydrops-like features and CDG-Ia have been reported. Two more unrelated patients with CDG-Ia who presented with hydrops fetalis are reported here, providing definite evidence that non-immune hydrops fetalis can be caused by CDG-Ia. The presence of congenital thrombocytopenia and high ferritin levels in both patients was remarkable. These might be common features in this severe form of CDG. Both patients had one severe mutation in the phosphomannomutase 2 gene, probably fully inactivating the enzyme, and one milder mutation with residual activity, as had the patients reported in literature. The presence of one severe mutation might be required for the development of hydrops fetalis. CDG-Ia should be considered in the differential diagnosis of hydrops fetalis and analysis of PMM activity in chorionic villi or amniocytes should also be considered.